2013
DOI: 10.1161/circulationaha.112.001088
|View full text |Cite
|
Sign up to set email alerts
|

Variation Exists in Rates of Admission to Intensive Care Units for Heart Failure Patients Across Hospitals in the United States

Abstract: Background Despite increasing attention on reducing relatively costly hospital practices while maintaining the quality of care, few studies have examined how hospitals use the intensive care unit (ICU), a high-cost setting, for patients admitted with heart failure (HF). We characterized hospital patterns of ICU admission for patients with HF and determined their association with the use of ICU-level therapies and patient outcomes. Methods and Results We identified 166,224 HF discharges from 341 hospitals in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 36 publications
(27 reference statements)
3
81
1
1
Order By: Relevance
“…Moreover, Goldman et al 21 demonstrated that POA codes were very accurate when compared with direct medical record abstraction, suggesting that the PE cases identifi ed in this study represent PEs diagnosed on admission. Finally, our study is limited to patients with PE, and although it complements previous work among patients with other conditions, [4][5][6] further work is necessary to assess the validity of these fi ndings in patients without PE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Goldman et al 21 demonstrated that POA codes were very accurate when compared with direct medical record abstraction, suggesting that the PE cases identifi ed in this study represent PEs diagnosed on admission. Finally, our study is limited to patients with PE, and although it complements previous work among patients with other conditions, [4][5][6] further work is necessary to assess the validity of these fi ndings in patients without PE.…”
Section: Discussionmentioning
confidence: 99%
“…29 However, past work demonstrates that ICU admission may be more discretionary for patients at lower risk. 4,5,30 Chen et al 30 evaluated patients admitted to Veterans Administration hospitals and found signifi cant variation in ICU admission rates between hospitals that persisted aft er adjustment for both predicted mortality on admission and admission diagnosis. In their mortality analysis, they found a protective eff ect of ICU admission but only at the highest rates of predicted mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 In brief, this dataset contains a date-stamped log of all items and services charged to the patient or his/her insurer, including medications, laboratory, and ventilation therapies at the individual patient level. Hospitals in the dataset represent all regions of the United States, are predominantly small-to medium-sized nonteaching facilities, and serve mostly urban patient populations.…”
Section: Design Study Setting and Subjectsmentioning
confidence: 99%
“…1 In this role, physicians are often the final arbiter regarding the wise and efficient use of medical resources. 2 Wasteful medical practices have been documented in virtually every aspect of medical care, [3][4][5][6] accounting for nearly 30 % of all medical expenditures. 7 Recent policy interventions that aim to encourage more cost-efficient practice among physicians include promoting transparency (publishing cost or quality outcomes), pay for performance, payment bundling and shared financial risk models.…”
Section: Introductionmentioning
confidence: 99%